The Influence of Lowness of Ufuk in Reckoning of Maghrib Prayer Times at City’s Grand Mosque in Indonesia - Masruhan Masruhan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
The treasure of the reckoning time of Maghrib prayer in the study of astronomy has a variety of criteria in determining the height of the Sun, namely: rounding the number -1° and the formulation of the Sun's height: - (horizon + semidiameter + refraction low). This study discusses the implementation of these two criteria into the reckoning time of prayer at the city/regency Grand Mosque. This research is library research, using quantitative descriptive analysis. This results showed namely: the results of testing the accuracy of the reckoning of the criteria prayer time ho = -1 ° slower in Maghrib time if the input height is below 33 masl. Then the results of the reckoning prayer time criteria ho = -1 ° have the results of the Maghrib time which is the same as the reckoning criteria ho = - (ku + ref + sd) when the input height is 33 masl. And the results of the reckoning time criteria ho = -1 ° faster at Maghrib time which is above 33 masl. While the tolerance limit of a difference of 1 minute is reaching an altitude of 201 masl means that a total of 82.14971% of the total Grand Mosque of the City is still safe. In Indonesia, the height of the Great Mosque of the City above 201 masl or the difference of more than 1 minute is 17,850287%, which means that it is still not safe to use the initial reckoning when the criteria are ho = -1° and it is necessary to add corrections to horizon modesty (place height).